O PODZIALE RZECZY I ICH PRZYMIOTACH. 8 TYTUŁ 1 KSIĘGI DIGESTÓW. TEKST − TŁUMACZENIE − KOMENTARZ - Tarwacka, Anna (Zeszyty Prawnicze, 2017)
O PODZIALE RZECZY I ICH PRZYMIOTACH. 8 TYTUŁ 1 KSIĘGI DIGESTÓW. TEKST − TŁUMACZENIE − KOMENTARZ